Portfolio choice of financial investors and European business cycle convergence: A panel analysis for EU countries - Ansgar Belke; Jennifer Schneider (Research On Money in the Economy (ROME), 2013)
We investigate the linkage between business cycle convergence and financial portfolio choice for a panel of 18 EU countries. We construct an index of similarity of financial portfolios which we then put into context with the view that 'the financial world' has an impact on business cycles and contributes to business cycle convergence via the consumption-wealth linkage. The model which guides our analysis is the International Asset Pricing Model (IAPM). Portfolios of the 18 EU countries investigated by us turn out to become more similar over time. According to our fixed effects GMM TSLS estimations, similar portfolios contribute to a convergence of business cycles - via a convergence of consumption cycles. This turns out to be especially true for country-pairs that include euro area non-member countries and, thus, have quite different income and wealth structures.
Keywords: E21; F36; G11; O47; 330; business cycle convergence; consumption-wealth linkage; International Asset Pricing Model; portfolio choice; panel methods; specialisation index